Potret Matrilineal Minangkabau dalam Novel Segala Yang Diisap Langit Karya Pinto Anugrah - Karuniawan, Dwiky Yoga; Ririe Rengganis (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
This study discusses the portrait of Minangkabau matrilineality as represented in the novel Segala Yang Diisap Langit. The aim of this research is to describe the forms of Minangkabau matrilineal structure and its impacts as depicted in Segala Yang Diisap Langit, a novel by Pinto Anugrah. The study employs a descriptive-analytical method with literary anthropology and literary sociology approaches. The data consist of sentences in the novel that reflect aspects of Minangkabau matrilineality. The data source is the novel Segala Yang Diisap Langit by Pinto Anugrah. The data collection technique used is observation and note-taking. Data were analyzed using content analysis techniques linked to the research topic. The results of the study reveal various forms of Minangkabau matrilineality in the novel, including daughters as heirs of the family lineage, the representation of rumah gadang as the center of family civilization, women as holders of social structures, and exogamous marriage practices. Additionally, the novel portrays challenges within the matrilineal system, such as conflicts of interest and clashes between tradition and modern values. Keywords: matrilineal, Minangkabau, segala yang diisap langit novel